Serum sphingomyelin has potential to reflect hepatic injury in chronic hepatitis B virus infection - Su-Jun Zheng; Feng Qu; Jun-Feng Li; Jing Zhao; Jing-Yun Zhang; Mei Liu; Feng Ren; Yu Chen; Jin-Lan Zhang; Zhong-Ping Duan (International Journal of Infectious Diseases, 2015)
Objective: To explore the relation between serum sphingolipids and hepatic injury in chronic HBV infection. Methods: A cohort of participants including 48 healthy persons, 103 chronic HBV-infected patients containing chronic hepatitis B (CHB) and HBV-related cirrhosis were included. High performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) was performed to detect serum sphingolipids. The serological indicators were detected and quantified. The valid liver biopsy specimens were acquired from twenty five CHB. Results: Twenty four serum sphingolipids were detected. There were eighteen sphingolipids showing significant differences between the healthy control and chronic HBV infection groups. In patients with chronic HBV infection, fourteen sphingolipids differed significantly between CHB and HBV-related cirrhosis. Among sphingolipids with a significant difference in both HBV infection vs healthy control and CHB vs cirrhosis, seven sphingolipids were independently related to the presence of cirrhosis. SM(d18:1/24:0), a sphingomyelin (SM) compound, was found to have a negative correlation with model for end-stage liver disease (MELD) score. Additionally, SM(d18:1/24:0) was demonstrated to have a correlation with inflammation grades by liver biopsy in CHB patients. Conclusions: Serum sphingolipids have close relation with hepatic injury in chronic HBV infection, especially that SM(d18:1/24:0) might be a potential serum biomarker.